2019
DOI: 10.1007/s11069-019-03613-4
|View full text |Cite
|
Sign up to set email alerts
|

Traditional prediction of drought under weather and climate uncertainty: analyzing the challenges and opportunities for small-scale farmers in Gaza province, southern region of Mozambique

Abstract: This paper explores the traditional indicators that small-scale farmers in Gaza province in southern Mozambique use to predict drought events on their rain-fed farms. It analyzes the contextual situation regarding the accuracy and reliability of the traditional prediction methods under the current weather and conditions of climate uncertainty and variability, and the opportunities that their prediction methods can bring to reduce their current and future exposure and vulnerabilities to drought. Farmers use a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Taken together, the normative barriers in the context of such studies refer to erroneous and institutionalized norms of meteorological information usage in some agricultural communities. This problem has been reported as a major obstacle, especially in most developing and underdeveloped countries, see [1,53,55]. Sharifzadeh et al [1], in an actor-network analysis of weather information in Iran, revealed that social norms of farming communities have negative impacts on the adoption of these services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, the normative barriers in the context of such studies refer to erroneous and institutionalized norms of meteorological information usage in some agricultural communities. This problem has been reported as a major obstacle, especially in most developing and underdeveloped countries, see [1,53,55]. Sharifzadeh et al [1], in an actor-network analysis of weather information in Iran, revealed that social norms of farming communities have negative impacts on the adoption of these services.…”
Section: Discussionmentioning
confidence: 99%
“…Kassem et al [53] reported similar results for the adoption of climate-related predictions in Egypt. Salite [55] also introduced the tradition and negative attitude towards new climate prediction systems as one of the main limiting factors of applying weather services in Mozambique. These incorrect individual and social norms have led to a kind of stereotype-centeredness in agricultural societies.…”
Section: Discussionmentioning
confidence: 99%
“…In our study sites, human observation of climate and the timing of seasonal activities (i.e., seasonal calendar) were found to be attuned with natural phenomenon and are in line with the weather patterns obtained from regional meteorological stations. Previous studies suggested that indigenous peoples in different settlements worldwide used various types of signs or indicators to interpret their surroundings, forecast resources, decide activities and predict environmental processes [26]. On the whole, they developed several categories of an indicator, including: Biological signs, such as behaviors of wild animals, reproduction and migration of birds and typical phenological phases of plants, and abiotic environmental conditions, such as temperature/ precipitation, a constellation of stars, cloud cover and type, and soil condition [5,27,47,51].…”
Section: Tek Based Observationsmentioning
confidence: 99%
“…Accordingly, such knowledge can help assess how the socio-cultural values of indigenous communities inform environmental management decisions [18]. Studies of indigenous communities in Africa [11,21], Asia [22,23], Australia [20], and South [18,24] and North America [25] all revealed that indigenous communities have utilized various ecological indicators and approaches based on TEK to predict weather conditions, interpret implications and assess their ecosystems and available resources [26]. Based on their TEK, indigenous people have shifted their crop type to adapt to climate change [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, many farmers and pastoralists in Africa are likely to suffer the most from direct and indirect climate change, owing to their close connection to the natural world and their condensed socio-ecological resilience (Zuma-Netshiukhwi et al, 2013). In Gaza province of Mozambique, it has been reported that the current irregularity and changes in weather and climate adversely bothered the interpretation, accuracy, and reliability of most of bio-physical indicators, and thus their farming activities (Salite, 2019).…”
Section: Introductionmentioning
confidence: 99%